Chemical constituents from the aerial parts of Clematis terniflora DC - Meng-Ya Chen; Zi-Han Zhu; Xin-Yu Yu; Ya-Ru Wu; Shi-Hui Qian; Zhen-Lin Li (Biochemical Systematics and Ecology, 2027)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Colloidal biochar promotes microbial carbon dioxide fixation and enhances net soil organic carbon gain - Jia Bing Liu; Jia Wang; Wang Kai Tong; Han Tang; Mei Ru Yue; Piao Yi Jiang; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Chemical Engineering, 2026)

The co-ecotoxicity of microplastics and associated contaminants (PFOA) on soil ecosystems - Si-Yu Liu; Feng Han; Li-Qi Ma; Zheng Li; Chun-Ru Qin; Ikram Yaqine; Yi-kai Wang; Jian Su; Jie Chen (Journal of Environmental Chemical Engineering, 2026)

Mixed-gas nanobubble and colloidization stacked modification: Enhancing porous/chemical properties and endowing rapid adsorption function of biochar - Mei Ru Yue; Han Tang; Wang Kai Tong; Jia Bing Liu; Piao Yi Jiang; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Chemical Engineering, 2026)

Novel temperature-tolerant Schiff base derivative as high-efficiency inhibitor for acid corrosion of N80 steel - Li-Mao Chen; Shuang-Jian Li; Ru-Han Li; Bo-Kai Liao; Xing-Peng Guo; Long-Fei Song (Chemical Engineering Journal, 2026)

Microbial and environmental determinants of 1-propanol biosynthesis in Jiang-flavor Baijiu fermentation - Wei-Tao Zhai; Han Zhao; Li-Juan Chai; Wei Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Chuan-Qiang Gao; Guan-Ru Si; Wen-Qing Zhang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Microbiology, 2026)

Heterolytic urea exchange-mediated thermal locking: Architecting 3D printed photo-mechanochromic smart elastomers - Min Yu; Yeting Huang; Dong Wang; Ru Song; Hanzhao Gong; Shuming Zhang; Xiaoyu Han; Yangzheng Li (Chemical Engineering Journal, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Microplastics Inhibit Microbial Abundance and Enzyme Activities in Pb/Cd Co-contaminated Soil: The Alleviating Role of Biochar - Si-Yu Liu; Feng Han; Li-Qi Ma; Zheng Li; Chun-Ru Qin; Ikram Yaqine (Journal of Soil Science and Plant Nutrition, 2026)

Coupling microbial electrosynthesis and chain elongation for simultaneous biomethane upgrading and carboxylate recovery: A tunable carbon valorization strategy - Kai-Kai Wu; Shu-tong Wu; Chuan Chen; Zi-Han Wang; Ya-Ru Wang; Li Zhao; Juan Tong; Fei Shen; De-Feng Xing; Nan-Qi Ren; Lei Zhao (Water Research, 2026)

Foc4-Ap1, a putative aspartic protease of Fusarium oxysporum f. sp. cubense race 4, targets banana NAD(P)H-quinone oxidoreductase subunit S to promote virulence - Ru-Jing Zeng; Wen-Jing Chen; Zheng Li; Huan-Cai Ou; Qing-Dong Chen; Mei Luo; Han-Da Song; Zhang-Yong Dong (Physiological and Molecular Plant Pathology, 2026)

Constructing compatible LLZTO/PEO interfaces with fast Li+ transport channels for high-performance composite polymer electrolytes - Yimei Jin; Yiting Lin; Zekai Zhang; Bing Li; Ru Wang; Cheng Lian; Xia Han; Honglai Liu; Haiping Su; Jingkun Li (Chemical Engineering Journal, 2026)

Liquid-phase hydrogenation of benzaldehyde to benzyl alcohol over NiCoAl‑R catalysts: Synergistic metal–metal oxide interfaces for enhanced catalytic performance - Lingmei Yang; An Wei; Ru kuan Liu; Guo ling Zhang; Bing Han; Baining Lin; Lianhua Li (Journal of Environmental Chemical Engineering, 2026)

AtGASA1 positively regulates Arabidopsis response to salt stress by suppressing accumulation of reactive oxygen species - Jian-Bo Song; Hao-En He; Cai-Feng Wang; Xian-Zhi Zuo; Zi-Xin Zhao; Ya-Ru Li; Yu-Fan Chen; Shu-Fan Liu; Han-Wen Guo; Xuan Huang (Plant Cell Reports, 2026)

Novel biodiversity and biogeography insights of filamentous Bangiales (Rhodophyta) from China - Yan-De Wang; Yin-Yin Deng; Cui-Cui Tian; Han-Ru Ge; Wei Zhou; Nan-Jing Ji; Li-En Yang (Algae, 2026)
The taxonomy of filamentous Bangiales was challenging due to its plastic and simple morphology. Molecular approaches play a significant role in revealing cryptic biodiversity and resolving phylogenetic relationships. Nonetheless, the biodiversity of filamentous Bangiales in many regions, including China, has not been thoroughly investigated yet using updated methods. In this study, we investigated the biodiversity of filamentous Bangiales in China, employing a more comprehensive and detailed sampling approach. The rbcL and 18S gene sequences (partial or complete) of 49 specimens collected from 37 sites were obtained. Phylogenetic analysis resolved these specimens into four clades, including Bangia, ‘Bangia’ 1, ‘Bangia’ 2, and Pseudoganglia. Seven putative species were delineated using empirical methods, including Automatic Barcode Gap Discovery (ABGD), General Mixed Yule Coalescent (GMYC), and Bayesian Poisson tree processes (bPTP), as well as genealogical analysis. Among them, four were species previously reported, two were cryptic species, and the other was a new record in China. The distribution of these molecularly delineated species was mapped along China’s coastline. Similar to the bladed Bangiales, antitropical, transoceanic, and thermal-gradient distribution patterns were also observed for filamentous Bangiales on a global scale. The ancestral region was retraced by incorporating species data from China into existing datasets using BioGeoBEARS with BAYAREALIKE + J as the best-supported model. Under this model, East Asia shows the highest marginal probability as the ancestral area for the crown clade, though uncertainty remains across alternative regions. A most parsimonious expansion scenario of Bangiales from east Gondwana to other regions of the world was proposed.

The role of artificial intelligence in advancing population-based cancer registration - Shuai Ding; Mingyuan Liu; Hao Wang; Cheng Song; Luyue Zhao; Zhihao Yang; Yue Wang; Yifan Wang; Haitao Cui; Zihao Liu; Dongrun Liu; Tomohiro Matsuda; et al. (Science Bulletin, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

3D Morphology Analysis and Shear Strength Prediction Model for a Backfill–Rock Interface - Wenkai Ru; Diyuan Li; Zhenyu Han; Pingkuang Luo; Hao Gong (Rock Mechanics and Rock Engineering, 2026)

Strength enhancement and microstructural observation of cement-stabilized calcareous sand by optimizing the preparation process - Weishen Li; Yang Wu; Xue Li; Han Ma; Yifei Ru; Xiangxing Ye (Journal of Cleaner Production, 2026)

Untargeted metabolomics elucidates the enhanced protective effects of blackberry juice fermented with Lacticaseibacillus paracasei on hypothalamic-pituitary-adrenal (HPA) axis neuronal dysfunction - Han Wu; Qing-Ru Di; Anthony Pius Bassey; Shu-Dong Xie; Maria G. Corradini; Jian-Zhong Zhou; Xiao-Li Liu (Food Chemistry, 2026)

Synergistic microbial co-culture of Saccharomyces cerevisiae and Clostridium kluyveri enhances ethyl hexanoate production for stable flavor synthesis in strong-flavor Baijiu - Qiumei Zhang; Ru Zhang; Xi Chen; Meiyue Han; Ya Zhang; Weiwei Li; Xiuting Li; Jianxiong Hao; Baoguo Sun (Food Bioscience, 2026)

Adsorption of Methylene Blue using Poly(N-vinylpyrrolidone)-Graphene Oxide Composite: Kinetics, Equilibrium, Thermodynamics, and Mechanisms - Xiaoya Li; Ru Zheng; Guangyu Duan; Zhanfang Cao; Kai Han; Hong Zhong; Xin Ma; Shuai Wang (Water, Air, & Soil Pollution, 2026)

Mixed gas nanobubbles promote microbial CO2 fixation: Universal verification, mechanism, and application - Jia Wang; Piao Yi Jiang; Jia Bing Liu; Han Tang; Wang Kai Tong; Jia Jie Zou; Mei Ru Yue; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Management, 2025)

Interactive effect of various fatty acids and the Maillard reaction of sesame meal enzymatic hydrolysates on aroma generation - Qing-qing Ruan; Bei-bei Hu; Kai-yue Su; Jun-ru Li; Wen-ting Yin; Zi-qi Han; Yu-xin Liu; Xiao-shuang Cai (Food Research International, 2025)

Pyrolysis behavior of local environmentally harmful Erigeron Canadensis L.: a kinetic model using thermogravimetric analysis and multi-prediction - Tianrui Han; Ke Xie; Xiaolei Ye; Lei Gao; Shenghui Guo; Haohang Ji; Juanjian Ru; Botao Gao; Li Yang (Biomass and Bioenergy, 2025)

Metagenome-assembled genomes reveal Pseudogracilibacillus amylolyticus sp. nov., a functional uncultured microorganism in high-temperature Daqu - Ai-Ping Lv; Ying-Han; Bao-Zhu Fang; Guo-Zheng Wang; Man-Chun Liu; Bing-Ru Bian; Zhuo-Huan Zheng; Kai Li; Bing-Yu Li; Jian-Yu Jiao; Lan Liu; Lei Dong; et al. (Systematic and Applied Microbiology, 2025)

Quaternary Glaciation Accelerates Speciation in Aquatic Snakes Through Recent Bottlenecks - Jin‐Long Ren; Rui‐Han Li; Ru‐Wan Jia; Zhi‐Tong Lyu; Chaochao Yan; Dechun Jiang; Ying‐Yong Wang; Jia‐Tang Li (Molecular Ecology, 2025)
Climatic fluctuations during glacial periods have profoundly shaped the demographic history and gene flow dynamics of many taxa. This study integrated high‐throughput sequencing of 67 individuals with comprehensive genomic analyses to investigate biogeographic patterns, genetic divergence and demographic trajectories in the Opisthotropis latouchii species complex, a group of mountain stream snakes distributed across Central China. Our analyses revealed substantial genetic divergence, identifying four distinct lineages, each confined to one of the four major mountain ranges in Central China, including one previously unrecognised species. These lineages exhibited distinct demographic signatures, with population bottlenecks occurring during Quaternary glaciations. Initial isolation in the glacial refugia of the southern regions of these mountains during the Late Pliocene was followed by postglacial expansions along a northward trajectory, with further divergence along a latitudinal gradient associated with mountain distribution. Notably, the mountain ranges of Central China acted as critical refugia during glacial periods, promoting rapid speciation, and as dispersal corridors during interglacial periods, facilitating range expansion and enabling recent gene flow. These findings highlight the profound impact of Quaternary climatic oscillations on genetic structure, demographic history and gene flow patterns of these endemic taxa.

Inhibition of the NLR pathway alleviates MAPK1 mutation-driven proliferation and differentiation deficits and enhanced apoptosis in P19 cells - Tingying Lei; Lei Liu; Fei Guo; Ru Li; Li Zhen; Fang Fu; Min Pan; Jin Han; Hang Zhou; Chunling Ma; Ruibin Huang; Xinyi Zhao; et al. (Tissue and Cell, 2025)

Enhancing soil carbon sequestration capacity: Synergistic effect of low-release biochar and autotrophic microbial agents over one year - Han Tang; Jiajun Hu; Yundong Liu; Bu Li; Jia Wang; Wang Kai Tong; Mei Ru Yue; Jia Jie Zou; Min-tian Gao; Saiwei Zhang; Nan Liu; Jixiang Li (Journal of Environmental Chemical Engineering, 2025)

Effect of multiscale interface roughness on shear behavior of backfill-rock specimen - Wenkai Ru; Diyuan Li; Zhenyu Han; Hao Gong; Jinyin Ma (International Journal of Rock Mechanics and Mining Sciences, 2025)

Exploring the quality changes of carp roes: perspective from flavor characteristics and microstructure - Gaomin Han; Qiqi Li; Hui Hong; Juan You; Tao Yin; Shanbai Xiong; Ru Liu (Food Research International, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Green manure roots return drives saline-alkali soil organic carbon accumulation via microbial necromass formation - Fangdi Chang; Hongyuan Zhang; Peiyi Zhao; Na Zhao; Jiashen Song; Ru Yu; Jing Wang; Xiquan Wang; Dongxun Han; Xiaodong Liu; Jie Zhou; Yuyi Li (Soil and Tillage Research, 2025)

Construction and optimization of low carbon-to-nitrogen ratio-adapted Chlorococcum-Bacteria symbiosis for energy-efficient wastewater remediation - Ru Yan; Han Ji; Zhuo-Chao Liu; Mei-Qi Ren; Shuai Wang; Li-Ming Yang; Dan Cui (Bioresource Technology, 2025)

Seismic risk and loss assessment models for highway continuous girder bridges in large-scale zones - Si-Qi Li; Peng-Fei Qin; Peng-Chi Chen; Yi-Ru Li; Jia-Cheng Han; Jian Zhong (Soil Dynamics and Earthquake Engineering, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Performance on the forward osmosis membrane with polyethersulfone supported layer modified by sulfonated carbon nanotubes for dyeing wastewater treatment - Hongtao Cui; Zhongyi Zhu; Fengjie Chen; Yuanyuan Han; Ru Li (Journal of Environmental Chemical Engineering, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Degradation-Resistant Biochar Improves Soil Organic Carbon Storage: Promoting Autotrophic Metabolism & Increasing Refractory Organic Carbon - Han Tang; Jiajun Hu; Bu Li; Yundong Liu; Wang Kai Tong; Mei Ru Yue; Jia Wang; Wenjuan Wang; Min-tian Gao; Nan Liu; Jixiang Li (Bioresource Technology, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Surface and interface modification of biochar based on thermal nanobubble water - Mei Ru Yue; Jia Bing Liu; Piao Yi Jiang; Wang Kai Tong; Han Tang; Jia Wang; Wenjuan Wang; Min-tian Gao; Nan Liu; Jiajun Hu; Jixiang Li (Journal of Environmental Chemical Engineering, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Recent duplications and rare structural variations revealed by comparative sequence analysis of low molecular weight glutenin subunits (LMW-GS) genes re-identified using LMWgsFinder in 26 genomes of the grass family - Shengli Zhang; Xiaojing Shan; Yun Wang; Tairui Lu; Daxing Xu; Han Gong; Yuchao Fan; Yuanyuan Guan; Junjie Zhao; Haili Sun; Dongfang Li; Haiyan Hu; et al. (Theoretical and Applied Genetics, 2025)

Intensive rotational grazing has positive effects on productivity of rangeland - Ping Ge; Jianguo Xue; Yaqian Ru; Yulin Li; Dongxu Li; Peng Han; Ang Li; Jianhui Huang (Agriculture, Ecosystems & Environment, 2025)

Interface selectivity-based biochar: Directional evolution of properties, application & carbon neutralization evaluation - Wang Kai Tong; Chaomeng Dai; Jiajun Hu; Mei Ru Yue; Yun Dong Liu; Bu Li; Jia Jie Zou; Jia Wang; Han Tang; Min-tian Gao; Yucang Liang; Wenjuan Wang; et al. (Chemical Engineering Journal, 2025)

Lifetime probabilities of developing and dying from cancer in China: comparison with Japan and the United States in 2022 - Qian Zhu; Yifei Yao; Ru Chen; Bingfeng Han; Shaoming Wang; Li Li; Kexin Sun; Rongshou Zheng; Wenqiang Wei (Science China Life Sciences, 2025)

Electrochemically enhanced micro-electrolytic ceramic substrate infiltration system as an efficient approach for treatment of imidacloprid wastewater - Ru Zhang; Weiwei Zhang; Chengcheng Bu; Guangyao Chen; Shuyun Li; Yuchen Han; Haibin Ma; Anyong Xu; Desheng Wang; Limin Ma (Environmental Monitoring and Assessment, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Investigation on the synergistic effects and thermokinetic analyses during co-combustion of corn stalk and polyethylene plastic: Effect of heating rate and placement method - Mengjie Liu; Bin Han; Jin Bai; Jiayao Ru; Xuetao Wang; Lili Xing; Haojie Li; Siyu Lv; Aopeng Gao; Yiming Wang; Lingxue Kong; Zongqing Bai; et al. (Fuel, 2025)

Aberrance of GAP43/p-GAP43 Closely Associates with the Pathology of Neuron Loss in Prion-Infected Rodent Models - Xiao-Xi Jia; Cao Chen; Chao Hu; Yue-Zhang Wu; Zhi-Yue Chao; Jia-Feng Zeng; Ru-Han A.; Dong-Hua Zhou; Yuan Wang; Wei-Wei Zhang; Kang Xiao; Li-Ping Gao; et al. (Molecular Neurobiology, 2025)

Protective role of Tongxinluo in mitigating myocardial fibrosis in mice with acute myocardial infarction via neuregulin-1 upregulation and Inhibition of endothelium-interstitial transition - Zhen Li; Yu-jie Yin; Ya-ru Wei; Yi Liu; Ning-xin Han; Xiao-qi Wang; Yuan-jie Hao; Ya-fen Wang; Yun-long Hou; Zhen-hua Jia (Journal of Molecular Histology, 2025)

Co-occurrence of mcr-9 and blaNDM-5 in Multidrug-Resistant Enterobacter hormaechei Strain Isolated from a Patient with Bloodstream Infection - Ru Li; Junfeng Wang; Weiting Zhang; Chenhao Zhao; Mingxiao Han; Hong Du; Haifang Zhang (Current Microbiology, 2025)

Synergistic toxicity of cadmium and triadimefon on the microbiota and health of Rana dybowskii tadpoles - Xiao-yun Han; Peng Guo; Qiu-ru Fan; Qing-bo Zhou; Ming-da Xu; Xin-zhou Long; Li-yong Cui; Qing Tong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Isoalcanivorax beigongshangi sp. nov., isolated from the fermented grains of Chinese baijiu - Tong-Xi Zhang; Yi-Ming Li; Hao-Yue Gu; Ru Zhang; Zhan-Bin Sun; Han-Xu Pan; Qing Ren (Antonie van Leeuwenhoek, 2025)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Comparative analysis of the fatty acid profiles in goat milk during different lactation periods and their interactions with volatile compounds and metabolites - Guang-qin Liao; Hao-lei Han; Tian-cai Wang; Hou-ru Li; Yong-zhong Qian; Mai-xun Zhu; Qi Jia; Jing Qiu (Food Chemistry, 2024)

Chemical constituents from Ficus tikoua and chemotaxonomic significance - Han-Lei Wang; Jing Lu; Xue-Lin Chen; Ru Li; Kun Zhang; Yu-Ling Guo; Xia Zhao; Yu-Mei Zhang (Biochemical Systematics and Ecology, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

Response model between nanobubble preparation parameters and properties: Controllable preparation & its application example - Xin Ru Feng; Jiajun Hu; Nan Liu; Wang Kai Tong; Mintian Gao; Chaomeng Dai; Yueming Han; Jixiang Li (Journal of Water Process Engineering, 2024)

Molecular epidemiological and clinical infection characteristics analysis of Ralstonia - Zhaojun Sheng; Jiaxin Li; Guojing Han; Ru Fan; Pingjun Zhu; Xiangqun Fang (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose This study was to clarify the molecular epidemiology and clinical infection characteristics of Ralstonia pickettii and establish sequence typing system. Methods 48 nonrepetitive Ralstonia pickettii strains were collected from January 2008 to December 2013 at the Chinese People’s Liberation Army General Hospital (PLAGH) and were identified through a specific PCR experiment, 16 S rDNA experiment and VITEK 2 system to compare the identification accuracy. The sequence types of the strains were analyzed by multilocus sequence typing (MLST) method. The antibiotic sensitivity of these strains was determined with disc diffusion tests and broth microdilution method. The clinical data of Ralstonia pickettii infected patients were collected. Results All of the 48 strains were identified as Ralstonia pickettii by VITEK 2 system. 30 and 34 strains were identified as Ralstonia pickettii by PCR and 16 S rDNA experiment respectively. ST9 was the most sequence types (STs) in these 18 STs of 42 strains. 42 strains were divided into 2 groups (A and B) and 18 genotypes. Ralstonia pickettii was sensitive to some cephalosporins, β-lactam/β-lactamase inhibitor, levofloxacin and trimethoprim/sulfamethoxazole. Cough, sputum, shortness of breath and pulmonary rales were the common clinical symptoms of most Ralstonia pickettii infected patients. Conclusion We established a sequence typing system with a relatively fine resolution and the PCR assay is a faster and more sensitive method for clinical identification of Ralstonia pickettii . ST9 is the most common sequence types of Ralstonia pickettii . The most common clinical characteristics of Ralstonia pickettii infected patients were cough, sputum, shortness of breath and pulmonary rales.

Green manure removal with reduced nitrogen improves saline-alkali soil organic carbon storage in a wheat-green manure cropping system - Fangdi Chang; Hongyuan Zhang; Na Zhao; Peiyi Zhao; Jiashen Song; Ru Yu; Zhengrong Kan; Xiquan Wang; Jing Wang; Hanjiang Liu; Dongxun Han; Xinya Wen; et al. (Science of The Total Environment, 2024)

Seismic hazard models for typical urban masonry structures considering optimized regression algorithms - Si-Qi Li; Yi-Ru Li; Jia-Cheng Han; Peng-Fei Qin; Ke Du (Bulletin of Earthquake Engineering, 2024)

Influence of labor migration on rural household food waste in China: Application of propensity score matching (PSM) - Guohui Shen; Xin Ru; Kunzhen Wang; Ziqi Li; Mingxue Yu; Lu Chen; Juan Han; Yanzhi Guo (Journal of Environmental Management, 2024)

Efficient electro-demulsification of O/W emulsions and simultaneous oil removal enabled by a multiscale porous biocarbon electrode - Kui Wang; Hailiang Zhao; Yingming Zhang; Xu Li; Mengyi Xu; Meirong Song; Guangxin Ru; Xiaolei Jiang; Xiuhong Zhu; Dandan Han; Yutao Dong; Kexin Shen; et al. (Chemical Engineering Journal, 2024)

An Ensemble CNOP Method Based on a Pre-Screening Mechanism for Targeted Observations in the South China Sea - Ru Wang; Qingyu Zheng; Wei Li; Guijun Han; Xuan Wang; Song Hu (Journal of Marine Science and Engineering, 2024)
The uncertainty in the initial condition seriously affects the forecasting skill of numerical models. Targeted observations play an important role in reducing uncertainty in numerical prediction. The conditional nonlinear optimal perturbation (CNOP) method is a useful tool for studying adaptive observation. However, the traditional CNOP method highly relies on the adjoint model, and it is difficult to find the global optimal solution. In this paper, a pre-screening and ensemble CNOP hybrid method called PECNOP is proposed to identify optimal sensitive areas in targeted observations. PECNOP is an adjoint-free method that captures global CNOP with high probability, which can effectively solve the two major problems faced by traditional CNOP methods. We evaluated the performance of PECNOP by building an observation simulation system consisting of an ocean model and data assimilation. One of the assimilation experiments was dedicated to evaluating the stability and effectiveness of PECNOP in extreme events. The results show that, compared with traditional methods, PECNOP can stably capture the global CNOP. Extra observations and assimilation in the optimal sensitive areas identified by PECNOP can effectively improve forecasting by about 20% within 30 days. Therefore, PECNOP has potential to reduce the initial error of numerical models, which is important for improving forecasting.

Circular economy strategies in supply chains, enhancing resource efficiency and sustainable development goals - Jing Qi Gao; Ding Li; Guang Hui Qiao; Qiao Ran Jia; Shi Ru Li; Han Lin Gao (Environmental Science and Pollution Research, 2024)

Soil microbial diversity and network complexity drive the ecosystem multifunctionality of temperate grasslands under changing precipitation - Changchun Zhai; Lili Han; Chao Xiong; Anhui Ge; Xiaojing Yue; Ying Li; Zhenxing Zhou; Jiayin Feng; Jingyi Ru; Jian Song; Lin Jiang; Yunfeng Yang; et al. (Science of The Total Environment, 2024)

Does biogas industrial policy promote the industrial transformation? - Erga Luo; Ru Yan; Yaping He; Zhen Han; Yiyu Feng; Wenrong Qian; Jinkai Li (Resources Policy, 2024)

Artificial light at night, MRI-based measures of brain iron deposition and incidence of multiple mental disorders - Jianbo Jin; Wenxing Han; Teng Yang; Zhihu Xu; Jin Zhang; Ru Cao; Yuxin Wang; Jiawei Wang; Xin Hu; Tiantian Gu; Fan He; Jing Huang; et al. (Science of The Total Environment, 2023)

Multivariate Sea Surface Prediction in the Bohai Sea Using a Data-Driven Model - Song Hu; Qi Shao; Wei Li; Guijun Han; Qingyu Zheng; Ru Wang; Hanyu Liu (Journal of Marine Science and Engineering, 2023)
Data-driven predictions of marine environmental variables are typically focused on single variables. However, in real marine environments, there are correlations among different oceanic variables. Additionally, sea–air interactions play a significant role in influencing the evolution of the marine environment. Both internal dynamics and external drivers contribute to these changes. In this study, a data-driven model is proposed using sea surface height anomaly (SSHA), sea surface temperature (SST), and sea surface wind (SSW) in the Bohai Sea. This model combines multivariate empirical orthogonal functions (MEOFs) with long and short-term memory (LSTM). MEOF analysis is used on the multivariate dataset of SSHA and SST, considering the correlation among sea surface variables. SSW is introduced as a predictor to enhance the predictability of the multivariate sea surface model. In the case of the Bohai Sea, the comparative tests of the model without wind field effect, the fully coupled model, and the proposed prediction model were carried out. MEOF analysis is employed in comparative experiments for oceanic variables, atmospheric variables, and combined atmospheric and oceanic variables. The results demonstrate that using wind field as a predictor can improve the forecast accuracy of SSHA and SST in the Bohai Sea. The root mean square errors (RMSE) for SSHA and SST in a 7-day forecast are 0.016 m and 0.3200 °C, respectively.

The sulfate assimilation and reduction of marine microalgae and the regulation of illumination - Wen-Ying Dai; Lu Han; Pei-Feng Li; Qin-Dao Li; Li-Jun Xie; Chun-Ying Liu; Jun-Ru Kong; Ru Jia; Dan-Yang Li; Gui-Peng Yang (Marine Environmental Research, 2023)

Enhanced encapsulation of lutein using soy protein isolate nanoparticles prepared by pulsed electric field and pH shifting treatment - Rui Wang; Man-Qin Zeng; Yu-Wei Wu; Yong-Xin Teng; Lang-Hong Wang; Jian Li; Fei-Yue Xu; Bo-Ru Chen; Zhong Han; Xin-An Zeng (Food Chemistry, 2023)

Human TRMT1 catalyzes m2G or m22G formation on tRNAs in a substrate-dependent manner - Qing-Ping Xiong; Jing Li; Hao Li; Zhi-Xuan Huang; Han Dong; En-Duo Wang; Ru-Juan Liu (Science China Life Sciences, 2023)

Exploration of using acoustic vibration technology to non-destructively detect moldy kernels of in-shell hickory nuts (Carya cathayensis Sarg.) - Qing-li Han; Bai-xue Long; Xue-jun Yan; Wu Wang; Feng-ru Liu; Xue Chen; Fei Ma (Computers and Electronics in Agriculture, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Effect of liver metastasis on the efficacy of immune checkpoint inhibitors in cancer patients: a systemic review and meta-analysis - Bao-Wen Tian; Cheng-Long Han; Han-Chao Wang; Lun-Jie Yan; Zi-Niu Ding; Hui Liu; Xin-Cheng Mao; Jin-Cheng Tian; Jun-Shuai Xue; Long-Shan Yang; Si-Yu Tan; Zhao-Ru Dong; et al. (Clinical & Experimental Metastasis, 2023)

Soil erosion effectively alleviated by Miscanthus sacchariflorus, a potential candidate for land deterioration improvement - Chu Zhao; Yu-han Nie; Jian-pan Xin; Xiao-yu Zhu; Yan Li; Ru-nan Tian (Rhizosphere, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

Study on of structural style of fault zone and reservoir characteristics in the northern slope of Tazhong Uplift, Tarim Basin, China - Rui Zhao; Yuan Kang; Jun Han; Xiuxiang Zhu; Teng Zhao; Yuqing Liu; Chongyang Xiao; Shang Deng; Zhixing Ru; Yingtao Li (Carbonates and Evaporites, 2023)

The effects of pulsed electric fields treatment on the structure and physicochemical properties of dialdehyde starch - Ying Li; Jin-Hua Wang; Yu Han; Fu-Hao Yue; Xin-An Zeng; Bo-Ru Chen; Man-Qin Zeng; Meng-Wai Woo; Zhong Han (Food Chemistry, 2023)

The status of the global food waste mitigation policies: experience and inspiration for China - Guohui Shen; Ziqi Li; Tiannuo Hong; Xin Ru; Kunzhen Wang; Yanting Gu; Juan Han; Yanzhi Guo (Environment, Development and Sustainability, 2023)
Food waste has become a significant challenge faced by the community with a shared future for mankind, and it has also caused a considerable impact on China's food security. Scholars across disciplines, international organizations, and especially policymakers are increasingly interested in food waste. Policies are seen as a powerful factor in reducing food waste, but current research on related policies is more scattered. This paper summarizes and analyzes the experiences of food waste policy development and implementation by systematically reviewing the studies on food waste reduction policies. The results of this paper's analysis show that current global food waste policies are focused at the national strategic level, with approaches such as legislation, food donation, waste recycling, awareness and education, and data collection. At the same time, we find that the current experience of developed countries in policy formulation and implementation is beneficial for policy formulation in developing countries. And taking China as an example, we believe that developing countries can improve food waste policies in the future by improving legislation, guiding the development of food banks, promoting social governance, and strengthening scientific research projects. These policies will all contribute strongly to global environmental friendliness. In addition, we discuss some of the factors that influence the development of food waste policies and argue that in the future, more consideration needs to be given to the effects of policy implementation and that case studies should focus more on developing countries. This will contribute to the global sustainable development process.

Effects of H2O2 acclimation on the growth, polysaccharide production and tolerance performance of Nostoc flagelliforme - Shu-ting Liu; Shuai Wang; Na Han; Meng-yuan Li; Jian Li; Yan-ru Li; Shi-ru Jia; Pei-pei Han (Algal Research, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Air pollution, greenness and risk of overweight among middle-aged and older adults: A cohort study in China - Wenxing Han; Zhihu Xu; Xin Hu; Ru Cao; Yuxin Wang; Jianbo Jin; Jiawei Wang; Teng Yang; Qiang Zeng; Jing Huang; Guoxing Li (Environmental Research, 2023)

Acute Toxicity of a Novel anti-fouling Material Additive DCOIT to Marine Chlorella sp - Jin-Chuang Ru; Xue-Li Zhao; Zhi-Han Cao; Cheng-Zhuang Chen; Ping Li; Zhi-Hua Li (Bulletin of Environmental Contamination and Toxicology, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

A New Scheme for Capturing Global Conditional Nonlinear Optimal Perturbation - Siyuan Liu; Qi Shao; Wei Li; Guijun Han; Kangzhuang Liang; Yantian Gong; Ru Wang; Hanyu Liu; Song Hu (Journal of Marine Science and Engineering, 2022)
Conditional nonlinear optimal perturbation (CNOP) represents the initial perturbation that satisfies a certain physical constraint condition, and leads to a maximum prediction error at the moment of prediction. The CNOP method is a useful tool in studying atmosphere and ocean predictability problems. Generally, the optimization algorithm based on the gradient of the cost function to compute CNOP requires an initial guess. The traditional scheme randomly chooses the initial guess of CNOP within the constraint range and therefore this scheme is called RIG-CNOP. However, the RIG-CNOP scheme reduces the probability of capturing the global CNOP in many cases, such as the prediction model is strongly nonlinear or long-term prediction is performed, or multiple extreme values existed in the cost function. Considering the limitations of the RIG-CNOP scheme, we propose a new initial guess selection scheme. In this scheme, we first pre-analyze a series of random initial guesses, and then, an optimal initial guess is selected. The above process replaces the initial guess selection scheme in the traditional scheme, which is called PAIG-CNOP. Numerical experiments are conducted utilizing the Lorenz-63 model. Also, to compare the performance of the PAIG-CNOP method with the RIG-CNOP method in capturing global CNOP, the CNOP and the maximum cost function value (MCFV) obtained by the filtering method (FM) are used as benchmarks (this value is called FMMCFV in brief). The experimental results show that even the prediction model is strongly nonlinear or the prediction time is long, or the cost function has multiple extreme values, the PAIG-CNOP method can capture the global CNOP with a high probability. The results show that the PAIG-CNOP method has a higher probability of capturing the global CNOP than the RIG-CNOP method. In addition, we use an ensemble-based technique in the computation of gradients, thus avoiding the use of adjoint techniques in the maximization process. Due to the attractive features of the new method, the PAIG-CNOP method is an efficient and useful method for solving CNOP, it can be more easily applied to obtain the global CNOP of operational prediction models.

Peripheral Administration of an Opioid Peptide Analog Ameliorates Morphine-Produced Hyperalgesia in a Spared Nerve Injury Model - Yuan Wang; Meng-tao Ma; Jing Wang; Chao-zhen-yi Han; Kai Li; Qiao-min Ru; Na Li; Xin Liu; Rui Wang (International Journal of Peptide Research and Therapeutics, 2022)

Pleosporalins H and I, two new heptaketides from the endophytic fungus Pleosporales sp. F46 by using OSMAC strategy - Hong-Xia Yang; Xiao-Ping Peng; Han Gao; Hui-Min Zhang; Zi-Ru Wang; Gang Li; Hong-Xiang Lou (Natural Product Research, 2021)

Expression of the SPL-like gene LaSPL9 in Japanese larch (Larix leptolepis) is regulated by miR156 during somatic embryogenesis - Li-feng Zhang; Yan-ru Fan; Qian Lan; Li-wang Qi; Su-ying Han (Trees, 2021)

The Knowledge and Attitude Towards Advance Care Planning Among Chinese Patients with Advanced Cancer - Xiao-Ting Hou; Yu-Han Lu; Hong Yang; Ren-Xiu Guo; Yun Wang; Li-Hong Wen; Ya-Ru Zhang; Hong-Yu Sun (Journal of Cancer Education, 2021)

Prediction of oral hepatotoxic dose of natural products derived from traditional Chinese medicines based on SVM classifier and PBPK modeling - Size Li; Yiqun Yu; Xiaolan Bian; Li Yao; Min Li; Yan-Ru Lou; Jing Yuan; Hai-shu Lin; Lucy Liu; Bing Han; Xiaoqiang Xiang (Archives of Toxicology, 2021)

To the light side: molecular diversity and morphology of stomatopod larvae and juveniles (Crustacea: Malacostraca: Stomatopoda) from crustose coralline algal reefs in Taiwan - Kingsley J. H. Wong; Yao-Feng Tsao; Pei-Chen Tsai; Wei-Peng Hsieh; Han-Ru Li; Ryuji J. Machida; Benny K. K. Chan (Marine Biodiversity, 2021)

TRIP13 promotes the proliferation and invasion of lung cancer cells via the Wnt signaling pathway and epithelial–mesenchymal transition - Zhi-Han Li; Lei Lei; Liang-Ru Fei; Wen-Jing Huang; Yi-Wen Zheng; Mai-Qing Yang; Zhao Wang; Chen-Chen Liu; Hong-Tao Xu (Journal of Molecular Histology, 2021)

Compound heterozygous mutation of the ASXL3 gene causes autosomal recessive congenital heart disease - Fang Fu; Ru Li; Ting-ying Lei; Dan Wang; Xin Yang; Jin Han; Min Pan; Li Zhen; Jian Li; Fa-tao Li; Xiang-yi Jing; Dong-zhi Li; et al. (Human Genetics, 2021)

Impaired Parahippocampal Gyrus–Orbitofrontal Cortex Circuit Associated with Visuospatial Memory Deficit as a Potential Biomarker and Interventional Approach for Alzheimer Disease - Lin Zhu; Zan Wang; Zhanhong Du; Xinyang Qi; Hao Shu; Duan Liu; Fan Su; Qing Ye; Xuemei Liu; Zheng Zhou; Yongqiang Tang; Ru Song; et al. (Neuroscience Bulletin, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Synthesis and bioactivities of phenazine-1-carboxylic piperazine derivatives - Fei Han; Ru Yan; Min Zhang; Zhu Xiang; Qinglai Wu; Junkai Li (Natural Product Research, 2020)

LaMIR166a-mediated auxin biosynthesis and signalling affect somatic embryogenesis in Larix leptolepis - Zhe-Xin Li; Yan-Ru Fan; Shao-Fei Dang; Wan-Feng Li; Li-Wang Qi; Su-ying Han (Molecular Genetics and Genomics, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Zircon U–Pb dating of eclogite from the Qiangtang terrane, north-central Tibet: a case of metamorphic zircon with magmatic geochemical features - Qing-guo Zhai; Bor-ming Jahn; Xian-hua Li; Ru-yuan Zhang; Qiu-li Li; Ya-nan Yang; Jun Wang; Tong Liu; Pei-yuan Hu; Suo-han Tang (International Journal of Earth Sciences, 2017)

Improved salt tolerance of medicinal plant Codonopsis pilosula by Bacillus amyloliquefaciens GB03 - Qing-Qing Han; Yong-Na Wu; Hui-Juan Gao; Rui Xu; Paul W. Paré; Huazhong Shi; Qi Zhao; Hui-Ru Li; Sardar Ali Khan; Yin-Quan Wang; Suo-Min Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2017)

Altered Resting-State Signals in Patients with Acute Stroke In or Under the Thalamus - Lijun Chen; Chuanfu Li; Jian Zhai; Anqin Wang; Qin Song; Ying Liu; Ru Ma; Long Han; Yamikani Ndasauka; Xiaoming Li; Hai Li; Xiaochu Zhang (Neuroscience Bulletin, 2016)

Over-expression of miR166a inhibits cotyledon formation in somatic embryos and promotes lateral root development in seedlings of Larix leptolepis - Zhe-Xin Li; Shui-Gen Li; Li-feng Zhang; Su-ying Han; Wan-Feng Li; Hai-yan Xu; Wen-hua Yang; Ya-li Liu; Yan-ru Fan; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

Induced growth promotion and higher salt tolerance in the halophyte grass Puccinellia tenuiflora by beneficial rhizobacteria - Shu-Qi Niu; Hui-Ru Li; Paul W. Paré; Mina Aziz; Suo-Min Wang; Huazhong Shi; Jing Li; Qing-Qing Han; Shi-Qian Guo; Jian Li; Qiang Guo; Qing Ma; et al. (Plant and Soil, 2016)

Detection of gas hydrate sediments using prestack seismic AVA inversion - Ru-Wei Zhang; Hong-Qi Li; Bao-Jin Zhang; Han-Dong Huang; Peng-Fei Wen (Applied Geophysics, 2015)

Effects of extremely low frequency alternating-current magnetic fields on the growth performance and digestive enzyme activity of tilapia Oreochromis niloticus - Ying Li; Bixiao Ru; Xingfa Liu; Wei Miao; Kai Zhang; Lili Han; Haijun Ni; Hongjuan Wu (Environmental Biology of Fishes, 2015)

Deletion of RBP-J in dendritic cells compromises TLR-mediated DC activation accompanied by abnormal cytoskeleton reorganization - Yun-Ru Chen; Fan Feng; Li Wang; Shuo-Yao Qu; Zhen-Qiang Zhang; Li Liu; Hong-Yan Qin; Ying-Min Liang; Hua Han (Molecular Biology Reports, 2013)

Mutations in AP22.65 accelerate flowering in Arabidopsis thaliana - Ji Hong Xing; Feng Ru Wang; Jiao Jia; Jing Zhang; Li Li; Zhan Chen; Qiao Yun Weng; Ping Yang; Ye Zhang; Bin Zhao; He Long Si; Jin Gao Dong; et al. (Journal of Plant Biology, 2013)

Simultaneous Expression of Spinacia oleracea Chloroplast Choline Monooxygenase (CMO) and Betaine Aldehyde Dehydrogenase (BADH) Genes Contribute to Dwarfism in Transgenic Lolium perenne - Yongxia Bao; Ru Zhao; Feifei Li; Wei Tang; Liebao Han (Plant Molecular Biology Reporter, 2011)

Earthquake characteristics and building damage in high-intensity areas of Wenchuan earthquake I: Yingxiu town - Chang-Rong He; Ru Zhang; Qun Chen; Sheng-Li Han (Natural Hazards, 2011)

Earthquake characteristics and building damage in high-intensity areas of Wenchuan earthquake II: Dujiangyan and Pengzhou City - Chang-Rong He; Qun Chen; Sheng-Li Han; Ru Zhang (Natural Hazards, 2011)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

Ectopic Expression of the Tomato Mi-1 Gene Confers Resistance to Root Knot Nematodes in Lettuce (Lactuca sativa) - Li-Ying Zhang; Yu-Yang Zhang; Ru-Gang Chen; Jun-Hong Zhang; Tao-Tao Wang; Han-Xia Li; Zhi-Biao Ye (Plant Molecular Biology Reporter, 2010)

CISK kelvin wave with evaporation-wind feedback and air-sea interaction-A further study of tropical intraseasonal oscillation mechanism - Chongyin Li; Han-Ru Cho; Jough-Tai Wang (Advances in Atmospheric Sciences, 2002)

Development and propagation of equatorial waves - Xiao fan Li; Han-Ru Cho (Advances in Atmospheric Sciences, 1997)